Starting point: Motivation for choosing a degree in education - Britta Fischer; Miriam Bisterfeld (Forum Neue Medien in der Lehre Austria, 2015)
The motivation for choosing a particular degree is known to have an influence on the professional development of preservice teachers. As part of the quality improvement of the university training of physical eduaction (PE) students, this study compares the motivation of PE students for choosing a degree in education (subject-specific) with the motivation of student teachers in general (non-subject-specific). Overall, this study only detected minor differences regarding individual motivational facets. Thus, the starting points identified for the facilitation of professional development can be regarded as valid across disciplines. 16.12.2015 | Britta Fischer & Miriam Bisterfeld (Köln)